2006
DOI: 10.1002/dmrr.711
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐shock protein peptide DiaPep277 treatment in children with newly diagnosed type 1 diabetes: a randomised, double‐blind phase II study

Abstract: One-year treatment with DiaPep277 at a dosage of 1 mg is safe for use and well tolerated in children with recent-onset T1DM. However, it appears to have no beneficial effect in preserving beta-cell function or improving metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 20 publications
2
63
1
2
Order By: Relevance
“…Residual insulin secretion facilitates metabolic control and decreases the risk of keto-acidosis [3], and even modest beta cell function, with stimulated C-peptide above 0.2 nmol/l, may reduce long-term complications [4]. Type 1 diabetes is an autoimmune disease [5]; however, most attempts to use immune intervention to preserve residual beta cell function have achieved limited benefits or have been associated with adverse effects [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Treatment with anti-CD3 monoclonal antibodies appears to be the most promising treatment to date, but several patients treated in this way, as well as with anti-CD20 monoclonal antibodies, have experienced treatment-related adverse events [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Residual insulin secretion facilitates metabolic control and decreases the risk of keto-acidosis [3], and even modest beta cell function, with stimulated C-peptide above 0.2 nmol/l, may reduce long-term complications [4]. Type 1 diabetes is an autoimmune disease [5]; however, most attempts to use immune intervention to preserve residual beta cell function have achieved limited benefits or have been associated with adverse effects [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Treatment with anti-CD3 monoclonal antibodies appears to be the most promising treatment to date, but several patients treated in this way, as well as with anti-CD20 monoclonal antibodies, have experienced treatment-related adverse events [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if the tolerizing approach in mice may form the basis for the subsequent development of such a vaccine in humans, it is rather improbable that the same HSP60 peptide candidate will emerge as atherogenic in both species. However, promising results from clinical trials for treating rheumatoid arthritis and type I diabetes are currently ongoing (Prakken et al 2004;Raz et al 2001Raz et al , 2007Huurman et al 2007Huurman et al , 2008Lazar et al 2007;Koffeman et al 2009). A better understanding of these networks is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Primary outcome was glucagon-stimulated C-peptide at 10 months, which was higher in the DiaPep277 group than in the placebo group, an effect that was sustained with followup to 18 months (27). Four additional phase 2 studies showed results that were ambiguous at best, with no clear benefit (28)(29)(30). Nonetheless, the sponsor mounted two full-scale phase 3 trials.…”
Section: Misleading Pilot Studiesmentioning
confidence: 99%